High‐Performance Ultrathin Molecular Rectifying Diodes Based on Organic/Inorganic Interface Engineering. (27th October 2021) - Batista, Carlos Vinicius Santos; Merces, Leandro; Costa, Carlos Alberto Rodrigues; de Camargo, Davi Henrique Starnini; Bufon, Carlos César Bof
Abstract: The bottom‐up engineering of organic/inorganic hybrids is a crucial step toward advanced nanomaterial technologies. Understanding the energy level alignment at hybrid interfaces provides a valuable comprehension of the systems′ electronic properties – which are decisive for well‐designed device applications. Here, active interfaces of ultrathin (≈10 nm) molecular rectifying diodes that are capable of achieving a 4‐order‐magnitude rectification ratio along with 10 MHz cutoff frequency, both in a single nanodevice, are engineered. Atomic force microscopy and Kelvin‐Probe analysis are employed to investigate the surface potential of the hybrid devices′ organic/inorganic interfaces, which comprise a metal (M) electrode in contact with a few‐nanometer‐thick copper phthalocyanine (CuPc) film. Thereby a nanometer‐resolved quantification of the CuPc film work functions as well as the M/CuPc diode's space‐charge densities are delivered. By recognizing that the molecular rectifying diode is a functional building block for nanoscale electronics, the findings address crucial advances to the design of high‐performance molecular rectifiers based on organic/inorganic interface engineering. Abstract : The successful engineering of organic/inorganic hybrid nanodevices requires well‐established tools to bottom‐up manipulate functional interfaces. Here the advantage is taken of the Schottky diode working principle to build up ultrathin (≈10 nm) molecular rectifying diodes displaying cutting‐edge characteristics, such as a 10 MHz operation and a 4‐magnitude‐order rectification ratio. Such features raise the bar for the next‐generation ultrathin organic/inorganic devices.